Long-PCR based next generation sequencing of the whole mitochondrial genome of the peacock skate Pavoraja nitida (Elasmobranchii: Arhynchobatidae). (3rd March 2016) - Yang, Lei; Naylor, Gavin J. P.
Abstract: We determined the complete mitochondrial genome sequence (16, 760 bp) of the peacock skate Pavoraja nitida using a long-PCR based next generation sequencing method. It has 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region in the typical vertebrate arrangement. Primers, protocols, and procedures used to obtain this mitogenome are provided. We anticipate that this approach will facilitate rapid collection of mitogenome sequences for studies on phylogenetic relationships, population genetics, and conservation of cartilaginous fishes.